Nanomedicine - Winkler, L.; Woess, I.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Important and life-sustaining processes such as teh uptake, transport and metabolism of biologicla substances take place on cellular level in the human body. Diseases and disorders happening on this level can now be targeted with diagnostic and threapeutic tools in the nano-scaled size range.